Granule Mobility, Fusion Frequency and Insulin Secretion Are Differentially Affected by Insulinotropic Stimuli. (24th February 2015) - Schumacher, Kirstin; Matz, Magnus; Brüning, Dennis; Baumann, Knut; Rustenbeck, Ingo
Abstract : The pre‐exocytotic behavior of insulin granules was studied against the background of the entirety of submembrane granules in MIN6 cells, and the characteristics were compared with the macroscopic secretion pattern and the cytosolic Ca 2+ concentration of MIN6 pseudo‐islets at 22°C, 32°C and 37°C. The mobility of granules labeled by insulin–EGFP and the fusion events were assessed by TIRF microscopy utilizing an observer‐independent algorithm. In the z ‐dimension, 40 mm K + or 30 mm glucose increased the granule turnover. The effect of high K + was quickly reversible. The increase by glucose was more sustained and modified the efficacy of a subsequent K + stimulus. The effect size of glucose increased with physiological temperature whereas that of high K + did not. The mobility in the x / y ‐dimension and the fusion rates were little affected by the stimuli, in contrast to secretion. Fusion and secretion, however, had the same temperature dependence. Granules that appeared and fused within one image sequence had significantly larger caging diameters than pre‐existent granules that underwent fusion. These in turn had a different mobility than residence‐matched non‐fusing granules. In conclusion, delivery to the membrane, tethering and fusion of granules are differently affected by insulinotropic stimuli. Fusion rates and secretion do not appear to be tightly coupled. Abstract : The arrival of insulin granules at and departure from the plasma membrane is increased by glucose and high K +, accelerating the turnover. The number of granules remaining at the membrane decreases exponentially with time. The mobility pattern suggests that the majority of fusing granules is derived from long‐term resident granules, but a highly mobile fast‐fusing subgroup also exists. Increased cytosolic calcium affects fusion, but is not necessary for increased turnover. The actual secretion is additionally shaped by the heterogeneity of the post‐fusion fate of the granules and (possibly) oscillatory regulation of fusion.